Ярославль: [книга-альбом] / И. Н. Воейкова, В. П. Митрофанов - Воейкова Ираида Николаевна (Города-музеи, 1973)
Экземпляры: КХ (20140507) / Инвентарный номер: 563844 / Цена: 6.55 / Сис.шифр: 7С1 / Авт.знак: В 63 / ГРНТИ: 67.07 / ББК: 85